Recovering the unity of the Bible : one continuous story, plan, and purpose - Kaiser, Walter C., Jr. (Walter Christian), 1933- (Grand Rapids, Mich. : Zondervan, 2009)
Walter C. Kaiser challenges the common scholarly posture that sees mostly diversity throughout the biblical canon, pointing instead to the way several Biblical themes substantially support the case for unity, including: Messianic promises, the people of God, the law of God, the doctrine of salvation, the mission of the Old Testament. --from publisher description
Preface -- The unity of the Bible : introduction -- The unity of the Bible : diversity as an accompanying reality -- The harmonization of the diversity -- The unity of the Hebrew Bible -- The unity of the New Testament -- The unity of the Bible in its messianic promises -- The unity of the Bible between the two testaments : the God of the Old Testament and the new -- The unity of the Bible : two testaments : the morally offensive character and acts of Old Testament men and women -- The unity of the Bible and the people of God -- The unity of the Bible and its program : the Kingdom of God -- The unity of the Bible and the promise-plan of God -- The unity of the Bible and the law of God -- The unity of the Bible and the doctrine of salvation in both testaments -- The unity of the mission of the Old Testament -- The unity of the Bible and hermeneutics -- The unity of the Bible and expository preaching and teaching -- Epilogue.
Includes bibliographical references (p. 226-234) and indexes.
Keywords: Bible -- Criticism, interpretation, etc; Bible -- Theology